Genome Editing for Improving Crop Nutrition - Nagamine, Ai; Ezura, Hiroshi (Frontiers in Genome Editing, 2022)
Genome editing technologies, including CRISPR/Cas9 and TALEN, are excellent genetic modification techniques and are being proven to be powerful tools not only in the field of basic science but also in the field of crop breeding. Recently, two genome-edited crops targeted for nutritional improvement, high GABA tomatoes and high oleic acid soybeans, have been released to the market. Nutritional improvement in cultivated crops has been a major target of conventional genetic modification technologies as well as classical breeding methods. Mutations created by genome editing are considered to be almost identical to spontaneous genetic mutations because the mutation inducer, the transformed foreign gene, can be completely eliminated from the final genome-edited hosts after causing the mutation. Therefore, genome-edited crops are expected to be relatively easy to supply to the market, unlike GMO crops. On the other hand, due to their technical feature, the main goal of current genome-edited crop creation is often the total or partial disruption of genes rather than gene delivery. Therefore, to obtain the desired trait using genome editing technology, in some cases, a different approach from that of genetic recombination technology may be required. In this mini-review, we will review several nutritional traits in crops that have been considered suitable targets for genome editing, including the two examples mentioned above, and discuss how genome editing technology can be an effective breeding technology for improving nutritional traits in crops.